Alih Media Arsip Dinamis Inaktif ke CD_ROM di Kasubag Hukum Pengadilan Tinggi Padang - Fitri, Syafriati; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This article aims to reveal: (1) measures to transfer media to a CD ROM, (2) difficulties in transferring media. Data were collected through observation, interviews and work practices directly with the Pengadilan Tinggi, especially in the Kasubag Hukum. Analyzing data descriptively. Based on analyzing the data, it was concluded the following matters. First, the steps to transfer media to a CD ROM by way of: (1), setting up all the equipment such as computers, scan tool, software, (2) collect the files to be converted mediakan, (3) perform scanner perlembar the archive file has been collected, (4) switch archive files that have been scanned to PDF format, (5) file transfer activity that has shaped the PDF format in a CD ROM. Second, difficulties in implementing the law over the media in the Kasubag Hukum Pengadilan Tinggi Padang such as: (1) preparation tools, computer operations used frequently old or slow, a scan tool is used frequently jammed and slow because the tools used already in use for too long , (2) the file collection phase, takes a long time because they have to look for the sequence number archival storage boxes are not sequences in a year and types of cases, (3) the stage of scanning, archive will be scanned bound with rope and stamp affixed label Pengadilan Tinggi between the thread that binds the each sheet archives. Keywords: media, archives, dynamic, CD-ROM.